THE ROLE OF MATHEMATICAL MODELLING OF PRODUCTION PROBLEMS IN SPECIALIZED SCHOOL - Smagulov E. Zh.; Mendigaliyeva G. Kh.; Smagulov B. E. (International Journal of Innovative Technologies in Social Science, 2021)
The article discusses the main directions of the development of the educational environment and the role of mathematical modeling of production problems in a specialized school. The key issue of the modernization of education is described - this is improving its quality, bringing it in line with international standards. The emphasis is not on the knowledge gained, but rather on the process of applying this knowledge. The definition of the concept of pedagogical technology is given - this is information technology, since the basis of the technological process of training is the receipt and transformation of information.